Development and pilot testing of a health education program to improve immigrants' access to Canadian health services - Setareh Ghahari; Shawna Burnett; Libby Alexander (BMC, 2020)
Abstract Background In Canada's increasing immigrant population, a phenomenon called the "healthy immigrant effect" has arisen in which health declines after four years of settling. Access to healthcare is an important consideration. There is strong evidence that immigrants lack confidence and knowledge for navigating health services. The aim of this study was to develop and pilot test the Accessing Canadian Healthcare for Immigrants: Empowerment, Voice & Enablement (ACHIEVE) program. Method The study employed an exploratory sequential mixed methods design. A qualitative study was completed. Program content was developed based on a scoping review and refined in a formative evaluation. Then, a pilot test of the program measured participants' perceived efficacy in improving confidence in healthcare navigation, program satisfaction, and learning in individual sessions. Results Researchers found significantly higher rates of health navigation and an increase in knowledge about the Canadian health system post-program. Conclusions Results provide promising evidence that ACHIEVE may improve confidence in healthcare access among immigrants, demonstrating potential for dispersion on a larger scale.